A highly replicable decline in mood during rest and simple tasks - Jangraw, David C.; Keren, Hanna; Sun, Haorui; Bedder, Rachel L.; Rutledge, Robb B.; Pereira, Francisco; Thomas, Adam G.; Pine, Daniel S.; Zheng, Charles; Nielson, Dylan M.; Stringaris, Argyris (Nature human behaviour, 2023)
Does our mood change as time passes? This question is central to behavioural and affective science, yet it remains largely unexamined. To investigate, we intermixed subjective momentary mood ratings into repetitive psychology paradigms. Here we demonstrate that task and rest periods lowered participants’ mood, an effect we call ‘Mood Drift Over Time’. This finding was replicated in 19 cohorts totalling 28,482 adult and adolescent participants. The drift was relatively large (−13.8% after 7.3 min of rest, Cohen’s d = 0.574) and was consistent across cohorts. Behaviour was also impacted: participants were less likely to gamble in a task that followed a rest period. Importantly, the drift slope was inversely related to reward sensitivity. We show that accounting for time using a linear term significantly improves the fit of a computational model of mood. Our work provides conceptual and methodological reasons for researchers to account for time’s effects when studying mood and behaviour. In a series of experiments, Jangraw et al. show that people’s mood declines over time in common psychological tasks and during rest periods, but not in freely chosen behaviours.